Citrus aurantium L. var. amara Engl. inhibited lipid accumulation in 3T3-L1 cells and Caenorhabditis elegans and prevented obesity in high-fat diet-fed mice. (September 2019) - Shen, Chun-Yan; Wan, Lin; Wang, Tian-Xing; Jiang, Jian-Guo
Graphical abstract: Abstract: Natural products with anti-obesity effects and few side effects have attracted great attention recently. Citrus aurantium L. var. amara Engl. (CAVA) is popularly consumed as an edible and medicinal resource in China. However, its anti-obesity effects were poorly understood. The anti-obesity effects of CAVA extracts were systematically evaluated using 3T3-L1 cells, Caenorhabditis elegans ( C. elegans ) and high fat diet (HFD)-fed mice. Flavonoid-rich (EA) extracts with neohesperidin, hesperidin and naringin comprising 32.15%, were isolated from CAVA. EA extracts treatment significantly inhibited differentiation of 3T3-L1 preadipocytes by modulating lipid metabolism-related mediators. EA extracts supplementation also inhibited antioxidant responses in C. elegans by decreasing reactive oxygen species generation and malonaldehyde value, and increasing superoxide dismutase content. EA extracts feeding markedly decreased triglyceride (TG) content, and affected expression of genes involved in lipid and glucose metabolism in wild type C. elegans . TG content in mdt-15 (XA7702) mutants was not decreased by EA extracts administration, suggesting that EA extracts treatment might inhibit lipid accumulation in C. elegans dependent on mdt-15 . EA extracts intervention further reduced body weight gain and modulated plasma biochemical parameters in HFD-fed mice. EA extracts treatment prevented HFD-induced epididymal adipose hypertrophy, liver oxidative injuries and steatosis. EA extracts administration also strongly prevented HFD-induced reduction of gut microbial diversity, decreased the Firmicutes-to-Bacteroidetes ratio and the Erysipelotrichaceae abundance, and enhanced the Biﬁdobacteriace abundance in HFD-fed mice. EA extracts from blossoms of CAVA were excellent antiobesogenic candidates that acted through multiple mechanisms that acted simultaneously.